DPFC Performance with the Comparison of PI and ANN Controller - D Narasimha Rao; T Surendra; S Tara Kalyani (Institute of Advanced Engineering and Science, 2016)
Modern power systems demand the active control of power flow and for this purpose Power flow controlling devices (PFCDs) are required. Distributed FACTS Controller (DPFC) is a part of FACTS family. DPFC offers equal control ability same as UPFC, comprising the adjustment of the internal angle of the machine and bus voltage includes line impedance. In addition to UPFC a new device evolved known as DPFC in which common DC link is eliminated that enables the exclusive working between the two converters which are shunt and the series. The Distributed-FACTS (D- FACTS) idea is adopt in the series converter scheme. The replacement of the high rating three phase series converter with the multiple low rating single phase converters results in cost reduction and increases reliability greatly. The useful power transfer between the two converters which are shunt and series through common dc link in UPFC where as in DPFC in this the required power is transferred in the transmission line with three times of natural fundamental frequency. Where as in the new device no need of large voltage separation between the line and PFC Device is no requirement of high voltage isolation between because D-FACTS converters which are 1-ᴓ floating device with respect to the ground. Accordingly, In this paper we bring out the DPFC performance differences with different control techniques which are PI and Artificial Neural Network Controllers and bring with conclusion that ANN is a better control strategy compared to PI.